2020
DOI: 10.20535/2521-1943.2020.88.204782
|View full text |Cite
|
Sign up to set email alerts
|

Application of chemography for evaluating the workability of hard alloy cutting plates

Abstract: An approach to assessing the performance of carbide cutting inserts based on fixing changes in the defectiveness of its structure is proposed. The assessment is based on the phenomenon of activation of inhomogeneous chemical processes at extremely low concentrations of substances that occur in places of excessive surface activity in the structure of the material. The effect is determined by the initial imperfection of the structure of the surface layer of the material and the increase in the defectiveness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Crack detection is usually performed using microscopy (including electronic), using visualization tools. However, the detection of small cracks can be more effective using the chemography method [11,12]. The essence of the method consists in photographing oxidative reactions of ultra-low concentrations occurring on the surface of solids, and depending on the state of the surface and the conditions of its thermobaric loading at the previous stages.…”
Section: Development Of Damage To the Plate And Loss Of Its Performentioning
confidence: 99%
See 1 more Smart Citation
“…Crack detection is usually performed using microscopy (including electronic), using visualization tools. However, the detection of small cracks can be more effective using the chemography method [11,12]. The essence of the method consists in photographing oxidative reactions of ultra-low concentrations occurring on the surface of solids, and depending on the state of the surface and the conditions of its thermobaric loading at the previous stages.…”
Section: Development Of Damage To the Plate And Loss Of Its Performentioning
confidence: 99%
“…4) have shown that chemography can reveal zones on cutting plates that perceived the thermobaric load that occurred during operation (zones 1-4, 6), as well as an incipient main crack (zone 5). At the same time, in some zones (6, 7), blackness effects associated with contamination of the photographic plate were observed [11,12]. To establish the possible effect of coatings with a thickness of 3-10 μm on the surfaces of a hard-alloy plate on the form of chemographic images, special studies were carried out.…”
Section: Obtaining Chemographic Blackness When Changing the State mentioning
confidence: 99%